2012
DOI: 10.5216/cab.v13i2.9781
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho E Morfometria Duodenal De Frangos De Corte Submetidos a Diferentes Níveis De Energia E Programas De Alimentação De 42 a 57 Dias De Idade

Abstract: RESUMOO experimento foi realizado com o objetivo de avaliar diferentes níveis de energia e programas de alimentação sobre o desempenho, as características de carcaça e a morfometria da mucosa do duodeno de frangos de corte de 42 a 57 dias de idade. Foram utilizados 1.600 pintos machos "Cobb 500", em um delineamento inteiramente ao acaso, em esquema fatorial 2X4, sendo dois níveis de energia (3.200 e 3.600 kcal EM/kg) e quatro programas de alimentação. Os níveis energéticos ou os diferentes programas de aliment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
1
2
1
3
Order By: Relevance
“…Birds showed increased abdominal fat deposition when higher energy levels were provided in the diet, with the largest deposition of 4.05% at 3250 kcal.kg-1 ME. This disagrees with the findings of Duarte et al (2012), who evaluated the performance and duodenal morphometry of broiler chickens submitted to different energy levels and feeding programmes from 42 to 57 days old, in which the birds' abdominal fat percentage was not affected (P > 0.05 ) by the energy levels of the ration, levels of 3200 and 3600 kcal.kg-1 obtaining values of 2.00% and 2.14%, respectively. According to Oliveira Neto et al (2000) this may be associated with the reduced size of metabolically active organs and protein deposition in the breast observed in birds maintained at 32 ºC which provided greater amount of energy for deposition as fat in the heat environment.…”
Section: Resultscontrasting
confidence: 99%
“…Birds showed increased abdominal fat deposition when higher energy levels were provided in the diet, with the largest deposition of 4.05% at 3250 kcal.kg-1 ME. This disagrees with the findings of Duarte et al (2012), who evaluated the performance and duodenal morphometry of broiler chickens submitted to different energy levels and feeding programmes from 42 to 57 days old, in which the birds' abdominal fat percentage was not affected (P > 0.05 ) by the energy levels of the ration, levels of 3200 and 3600 kcal.kg-1 obtaining values of 2.00% and 2.14%, respectively. According to Oliveira Neto et al (2000) this may be associated with the reduced size of metabolically active organs and protein deposition in the breast observed in birds maintained at 32 ºC which provided greater amount of energy for deposition as fat in the heat environment.…”
Section: Resultscontrasting
confidence: 99%
“…Pelicano et al (2003) studied the intestinal morphometry of poultry on diets with different probiotics, and found that the highest value of crypt depth was related to an increased cell proliferative activity, the purpose of which is to ensure an adequate rate of epithelial renewal, offsetting losses in the heights of the villi. These results partially corroborate with an experiment conducted by Duarte et al (2012) who evaluated different energy levels (3200 and 3600 kcal/kg) and feeding programs, and noted that the highest level of energy led to a higher villus height and improved performance of the poultry.…”
Section: =098supporting
confidence: 80%
“…Em relação à gordura abdominal, os resultados deste estudo foram compatíveis com os dados obtidos por Duarte et al (2012), onde não houve efeito significativo entre os níveis de energia (3200 e 3600 kcal.kg -1 ) estudados para frangos de corte da linhagem Cobb de 42 a 57 dias de idade. Isto pode ter ocorrido devido ao curto período do experimento (14 dias), tempo insuficiente para ocorrer deposição de gordura abdominal.…”
Section: Methodsunclassified